Doctoral supervision in sport psychology: an asp-commissioned analysis of candidate satisfaction and experience - Lautenbach, Franziska; Elbe, Anne-Marie; Müller, Jana; Praisan, Gantima; Pizzera, Alexandra; Lohmann, Julia (Journal of applied sport and exercise psychology, 2025)
Good supervision plays a pivotal role in fostering a range of skills crucial for academic and professional growth. This study presents a subgroup analysis of previously published data (see Müller et al., 2023) and aims to investigate doctoral candidates in sport psychology with respect to their perception and satisfaction regarding supervision, as well as facets of their supervisory situation. A total of 70 doctoral candidates in sport psychology in Germany (Mage = 30.81 years; SDage = 3.60 years) provided information on their satisfaction with supervision and their perception of other facets of their supervisory situation (i. e., infrastructure, scientific work and thinking, relationship and health). Our results – which, due to incomplete data, do not consistently include all 70 participants – show that microecological (e. g., regular meetings, existence of a supervision agreement) and macroecological (i. e., time spent on doctoral research) aspects are positively related to doctoral candidates’ supervision satisfaction and their perception of other facets of the supervisory situation. Despite generally positive supervision, some expressed dissatisfaction, prompting recommendations for future improvements..